A Documentation Approach in The Design of A Wayang Kamasan Visual Archive Book as An Effort to Preserve Bali’s Traditional Visual Identity - Ananda Tanaya; Putri Dwitasari; Rabendra Yudistira Alamin; Sayatman (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
Wayang Kamasan painting is one of the traditional Balinese painting forms that possesses significant historical, philosophical, and artistic values, and serves as an important part of traditional visual identity. However, visual documentation of Wayang Kamasan artworks remains limited and has not yet been systematically organized into a sustainable visual archive. The lack of structured documentary media has caused the visual records, visual conventions, and distinctive characteristics of Wayang Kamasan to be at risk of degradation and the loss of their authentic values. This study aims to apply a qualitative visual documentation approach in the design process of a Wayang Kamasan visual archive book as an effort to preserve traditional visual identity. The method used employs experimental stages with a documentation approach that includes the systematic collection, recording, and processing of visual data. Data collection was conducted through visual observation, interviews with artists and cultural practitioners, literature studies, and direct photographic documentation of artworks located in museums, art studios, and private collections. Through this documentation approach, the visual archive book is expected to function not only as a medium for storing visual data, but also as a strategy for preserving the traditional visual identity of Wayang Kamasan so that its existence can be maintained and passed on to future generations.